Preparation method of titanium alloy cast ingot and product
By using automatic compounding and reverse segregation fabric technology in the preparation of titanium alloy ingots, combined with multiple smelting and turn-on furnace installation methods, the problems of gravity segregation and diffusion segregation in traditional titanium alloy ingots are solved, and large-scale casting is achieved The chemical composition uniformity and high strength of the ingot meet the needs of industrial production.
Patent Information
- Application Number
- CN202411382749.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
During the vacuum consumable arc smelting process, traditional titanium alloy ingots cause uneven distribution of Mo and Cr elements due to gravity segregation, forming β spots and component segregation, which is difficult to meet the requirements of high strength and high reliability, especially in large specifications. It is more difficult to control the components in the ingot.
The electrode block is prepared by automatic mixing of ingredients and large tonnage vertical hydraulic mechanism. The particle size and density of the intermediate alloy are controlled by batch fabric and reverse segregation fabric. The smelting process parameters are reasonably designed, such as reducing the smelting current and voltage, and multiple smelting and turnover are adopted. The furnace loading method controls the vacuum degree and cooling time, and suppresses gravity segregation and diffusion segregation.
The chemical composition uniformity of Ti1350 titanium alloy ingot with a diameter specification of Φ500mm~Φ780mm is achieved, which meets the requirements of industrial production, reduces gravity segregation and high-density inclusions, and improves the composition uniformity and quality of the ingot.
Smart Images

Figure CN119259959A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy material processing, and in particular to a method for preparing a titanium alloy ingot, and a product manufactured according to the method for preparing the titanium alloy ingot. Background Art
[0002] Ti1350 is an ultra-high-strength titanium alloy with a room temperature tensile strength of ≥1300MPa. It has the characteristics of high structural efficiency and high reliability and can be used to make various important load-bearing structural parts in aircraft landing gear, fuselage and wings.
[0003] Ti1350 is a β-type titanium alloy, containing 7 kinds of alloying elements, about 19%, including about 7% Mo and about 3% Cr. The density of single Mo is 10.2g / cm 3 , much higher than the titanium matrix density of 4.5g / cm 3 Therefore, in the molten state, under the influence of gravity, the Mo element tends to be enriched in the lower layer of the molten pool, and the enrichment degree increases with the deepening of the molten pool; and in the process of vacuum consumable arc melting, the electrode melts slowly from bottom to top, the molten pool exists for a long time, and the solid-liquid interface slowly migrates from bottom to top and from the edge to the core along the crucible. The longer molten pool existence time and the slower solidification rate leave enough space for the gravity sinking of the Mo element. Therefore, the gravity segregation element Mo content in the traditional melting ingot is often lower in the head of the ingot, and higher in the bottom. This inhomogeneity of alloy elements often leads to serious defects such as the formation of β spots or the composition exceeding the standard. The equilibrium concentration distribution coefficient of Cr element k = 0.56 is a typical positive segregation element. It will be enriched at the front of the solid / liquid interface during the solidification process of the alloy. Therefore, its macroscopic segregation degree is greatly affected by the depth of the molten pool. The deeper the molten pool, the longer the solidification distance of the grains, the more serious the diffusion segregation, and the formation of β spots that are harmful to the plasticity and fracture toughness of the alloy, which cannot meet the use requirements. The larger the size of the ingot, the larger and deeper the molten pool of vacuum consumable smelting will be, the more difficult it will be to suppress the inclusion of high-melting-point elements and the segregation of eutectoid elements, and the more difficult it will be to control the uniformity of the ingot composition. Summary of the invention
[0004] In order to overcome the defects of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing titanium alloy ingots, which can produce large-sized Ti1350 titanium alloy ingots with a diameter specification of Φ500mm~Φ780mm and uniform chemical composition, which is suitable for industrial production.
[0005] The technical solution of the present invention is: a method for preparing a titanium alloy ingot, which comprises the following steps:
[0006] (1) Raw material selection: Select sponge titanium, Al-85Mo master alloy, Al-70Cr master alloy, Al-85V master alloy, Al-75Nb master alloy, Ti-80Sn master alloy,
[0007] Al beans and sponge Zr are used as raw materials, among which the particle sizes of Al-85Mo, Al-85V and Al-75Nb master alloys are controlled at ≤0.8mm, ≤3.0mm and ≤1.2mm respectively, and the maximum particle size of other master alloys is ≤12mm;
[0008] (2) Preparation of electrode blocks: Electrode blocks are pressed using an automatic mixing and large-tonnage vertical hydraulic press. The pressing of each electrode block includes the following steps:
[0009] (2.1) Add a certain amount of titanium sponge to the bottom of the hydraulic press mold cavity and level it;
[0010] (2.2) Mix half the weight of titanium sponge and master alloy in a mixer and add them into the mold cavity of the hydraulic press;
[0011] (2.3) The mixer mixes the other half weight of titanium sponge and master alloy and adds them into the mold cavity of the hydraulic press;
[0012] (2.4) Start the large-tonnage hydraulic press to complete the pressing of a single electrode block;
[0013] (3) Electrode welding: Multiple electrode blocks are stacked and welded using argon protection in a vacuum plasma welding box to obtain a consumable electrode;
[0014] (4) Primary smelting: The consumable electrode is welded with the auxiliary electrode of the same brand in a vacuum consumable furnace, and then smelted. The smelting current is 9-14KA, the smelting voltage is 29-35V, the arc stabilization current is DC 6A-10A, the vacuum degree is controlled to be ≤10.0Pa during the smelting process, and the cooling time after smelting is ≥4 hours;
[0015] (5) Secondary smelting: After the first smelting, the ingot is turned over and loaded into the furnace. After auxiliary electrode welding, the second smelting is carried out. The smelting current is 13-18KA, the smelting voltage is 29-36V, the arc stabilization current is AC (10A-15)A / (6-10)s, the vacuum degree is controlled to be ≤5.0Pa during the smelting process, and the cooling time after smelting is greater than 5 hours;
[0016] (6) Tertiary smelting: After the secondary smelting, the ingot is turned over and loaded into the furnace. After auxiliary electrode welding, the third smelting is carried out. The smelting current is 9-14KA, the smelting voltage is 24-36V, the arc stabilization current is (7A-17)A / (4-8)s, the vacuum degree is controlled to be ≤2.0Pa during the smelting process, and the cooling time after smelting is greater than 7 hours;
[0017] (7) The smelted ingot is machined and the riser is removed to obtain the finished ingot.
[0018] Compared with the prior art, the invention has the following innovative features and beneficial effects:
[0019] 1. Since the density of Al-80Mo is 6.81g / cm 3 , the density of Al-85V is 5.14g / cm 3 , the density of Al-75Nb is 5.55g / cm 3 , which is much different from the density of titanium matrix (4.3g / cm 3 ), so in the molten state, these intermediate alloy particles will sink in the titanium solution, and there is a risk of gravity segregation and high-density inclusions due to the excessively fast sinking speed. Therefore, controlling the particle size of the high-density intermediate alloy can effectively prevent gravity segregation and high-density inclusions.
[0020] 2. When pressing the electrode block, each time the material is laid, the alloy with higher density is deposited at the bottom of the hydraulic press cavity. The alloy segregation problem can be improved by carrying out batch laying and reverse segregation laying on a single electrode. At the same time, a layer of sponge titanium is laid at the bottom of the hydraulic press cavity to prevent the micro-sized intermediate alloy containing the Mo element from falling to the bottom of the cavity through the gap during pressing, causing the loss of Mo element or the enrichment of Mo element, which makes it more difficult to control the Mo element composition. At the same time, the sponge titanium layer at the bottom of the electrode block acts as a buffer zone for the gravity sinking of gravity segregated elements during the vacuum consumable arc melting of titanium alloys, reducing the tendency of gravity segregated elements to enrich at the bottom of the molten pool.
[0021] 3. Reasonably design the smelting process parameters to reduce the depth of the molten pool during the smelting of large-sized ingots. Since the smelting current and voltage are positively correlated with the depth of the molten pool, when the smelting current is too large, the molten pool will be too deep, the diffusion and segregation of metal elements will be aggravated, and the columnar crystals tend to develop radially; but when the smelting current is too low, the molten pool will be imperfect, the surface quality of the ingot will be deteriorated, and it may cause insufficient alloying. Therefore, lower smelting currents and smelting voltages are used in the first, second and third smelting to reduce the depth of the molten pool, reduce the supercooling zone at the solidification front of the molten pool, and inhibit the diffusion and segregation of the Cr element. At the same time, the reduction in the depth of the molten pool also reduces the descending distance of the Mo element in the titanium matrix solution, inhibiting the gravity segregation of the Mo element; at the same time, the U-turn loading method is used in the second and third smelting to further homogenize the Mo element.
[0022] Also provided is a titanium alloy ingot manufactured by the method for preparing the titanium alloy ingot. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of longitudinal sampling of ingot.
[0024] Figure 2 Schematic diagram of nine-point transverse sampling of ingot.
[0025] Figure 3 The present invention is a flow chart of a method for preparing a titanium alloy ingot. DETAILED DESCRIPTION
[0026] like Figure 3 As shown, a method for preparing a Ti1350 titanium alloy ingot comprises the following steps:
[0027] (1) Raw material selection: Select sponge titanium, Al-85Mo master alloy, Al-70Cr master alloy, Al-85V master alloy, Al-75Nb master alloy, Ti-80Sn master alloy, Al bean, and sponge Zr with qualified composition as raw materials, wherein the particle sizes of Al-85Mo, Al-85V, and Al-75Nb master alloys are controlled to be ≤0.8 mm, ≤3.0 mm, and ≤1.2 mm, respectively, and the maximum particle size of other master alloys is ≤12 mm;
[0028] (2) Preparation of electrode blocks: Electrode blocks are pressed using an automatic mixing and large-tonnage vertical hydraulic press. The pressing of each electrode block includes the following steps:
[0029] (2.1) Add a certain amount of titanium sponge to the bottom of the hydraulic press mold cavity and level it;
[0030] (2.2) Mix half the weight of titanium sponge and master alloy in a mixer and add them into the mold cavity of the hydraulic press;
[0031] (2.3) The mixer mixes the other half weight of titanium sponge and master alloy and adds them into the mold cavity of the hydraulic press;
[0032] (2.4) Start the large-tonnage hydraulic press to complete the pressing of a single electrode block;
[0033] (3) Electrode welding: Multiple electrode blocks are stacked and welded using argon protection in a vacuum plasma welding box to obtain a consumable electrode;
[0034] (4) Primary smelting: The consumable electrode is welded with the auxiliary electrode of the same brand in a vacuum consumable furnace, and then smelted. The smelting current is 9-14KA, the smelting voltage is 29-35V, the arc stabilization current is DC 6A-10A, the vacuum degree is controlled to be ≤10.0Pa during the smelting process, and the cooling time after smelting is ≥4 hours;
[0035] (5) Secondary smelting: After the first smelting, the ingot is turned over and loaded into the furnace. After auxiliary electrode welding, the second smelting is carried out. The smelting current is 13-18KA, the smelting voltage is 29-36V, and the arc stabilization current is AC (10A-15)A / (6-10)s. The vacuum degree is controlled during the smelting process.
[0036] ≤5.0Pa, cooling time after smelting is greater than 5 hours;
[0037] (6) Tertiary smelting: After the secondary smelting, the ingot is turned over and loaded into the furnace. After auxiliary electrode welding, the third smelting is carried out. The smelting current is 9-14KA, the smelting voltage is 24-36V, the arc stabilization current is (7A-17)A / (4-8)s, the vacuum degree is controlled to be ≤2.0Pa during the smelting process, and the cooling time after smelting is greater than 7 hours;
[0038] (7) The smelted ingot is machined and the riser is removed to obtain the finished ingot.
[0039] Compared with the prior art, the invention has the following innovative features and beneficial effects:
[0040] 1. Since the density of Al-80Mo is 6.81g / cm 3 , the density of Al-85V is 5.14g / cm 3 , the density of Al-75Nb is 5.55g / cm 3 , which is much different from the density of titanium matrix (4.3g / cm 3 ), so in the molten state, these intermediate alloy particles will sink in the titanium solution, and there is a risk of gravity segregation and high-density inclusions due to the excessively fast sinking speed. Therefore, controlling the particle size of the high-density intermediate alloy can effectively prevent gravity segregation and high-density inclusions.
[0041] 2. When pressing the electrode block, each time the material is laid, the alloy with higher density is deposited at the bottom of the hydraulic press cavity. The alloy segregation problem can be improved by carrying out batch laying and reverse segregation laying on a single electrode. At the same time, a layer of sponge titanium is laid at the bottom of the hydraulic press cavity to prevent the micro-sized intermediate alloy containing the Mo element from falling to the bottom of the cavity through the gap during pressing, causing the loss of Mo element or the enrichment of Mo element, which makes it more difficult to control the Mo element composition. At the same time, the sponge titanium layer at the bottom of the electrode block acts as a buffer zone for the gravity sinking of gravity segregated elements during the vacuum consumable arc melting of titanium alloys, reducing the tendency of gravity segregated elements to enrich at the bottom of the molten pool.
[0042] 3. Reasonably design the smelting process parameters to reduce the depth of the molten pool during the smelting of large-sized ingots. Since the smelting current and voltage are positively correlated with the depth of the molten pool, when the smelting current is too large, the molten pool will be too deep, the diffusion and segregation of metal elements will be aggravated, and the columnar crystals tend to develop radially; but when the smelting current is too low, the molten pool will be imperfect, the surface quality of the ingot will be deteriorated, and it may cause insufficient alloying. Therefore, lower smelting currents and smelting voltages are used in the first, second and third smelting to reduce the depth of the molten pool, reduce the supercooling zone at the solidification front of the molten pool, and inhibit the diffusion and segregation of the Cr element. At the same time, the reduction in the depth of the molten pool also reduces the descending distance of the Mo element in the titanium matrix solution, inhibiting the gravity segregation of the Mo element; at the same time, the U-turn loading method is used in the second and third smelting to further homogenize the Mo element.
[0043] Preferably, in the step (2.1), 2 kg of sponge titanium is added to the bottom of the hydraulic press cavity and flattened; in the step (3), a consumable electrode with a diameter of Φ420 mm is obtained; in the step (4), the first smelting is carried out in a crucible with a diameter of Φ500 mm, the smelting current is 10 KA, the smelting voltage is 30 V, and the arc stabilizing current is 7 A DC; in the step (5), the second smelting is carried out in a crucible with a diameter of Φ580 mm, the smelting current is 14 KA, the smelting voltage is 32 V, and the arc stabilizing current is 12 A / 8 s AC; in the step (6), the third smelting is carried out in a crucible with a diameter of Φ680 mm, the smelting current is 12 KA, the smelting voltage is 26 V, and the arc stabilizing current is 9 A / 6 s; in the step (7), the smelted ingot is machined, the riser is cut off, and the diameter is Φ680 mm to obtain a Ti1350 finished ingot.
[0044] Preferably, in the step (2.1), 4 kg of sponge titanium is added to the bottom of the hydraulic press cavity and flattened; in the step (3), a consumable electrode with a diameter of Φ480 mm is obtained; in the step (4), the first smelting is carried out in a crucible with a diameter of Φ580 mm, the smelting current is 12KA, the smelting voltage is 32V, and the arc stabilizing current is DC 9A; in the step (5), the second smelting is carried out in a crucible with a diameter of Φ680 mm, the smelting current is 16KA, the smelting voltage is 34V, and the arc stabilizing current is AC 14A / 9s; in the step (6), the third smelting is carried out in a crucible with a diameter of Φ780 mm, the smelting current is 13KA, the smelting voltage is 28V, and the arc stabilizing current is 12A / 7s; in the step (7), the smelted ingot is machined and the riser is cut off to obtain a Ti1350 finished ingot with a diameter of Φ780 mm.
[0045] Also provided is a Ti1350 titanium alloy ingot manufactured by the method for preparing the titanium alloy ingot.
[0046] The specific embodiments of the present invention are described in detail below.
[0047] Implementation case 1: Φ680mm (weight 3-5 tons) ingot
[0048] 1. Raw material selection: Select sponge titanium, Al-85Mo master alloy, Al-70Cr master alloy, Al-85V master alloy, Al-75Nb master alloy, Ti-80Sn master alloy, Al bean, and sponge Zr with qualified ingredients as raw materials. The particle sizes of Al-85Mo, Al-85V, and Al-75Nb master alloys are controlled at ≤0.8mm, ≤3.0mm, and ≤1.2mm, respectively, and the maximum particle size of other master alloys does not exceed 12mm.
[0049] 2. Preparation of electrode blocks: Automatic mixing and large-tonnage vertical hydraulic press are used to press electrode blocks with a diameter of Φ420mm. The pressing of each electrode block includes the following four steps: 1) Add 2kg of sponge titanium to the bottom of the hydraulic press cavity and flatten it; 2) Mix half the weight of sponge titanium and intermediate alloy in a mixer and add them into the hydraulic press cavity; 3) Mix the other half the weight of sponge titanium and intermediate alloy in a mixer and add them into the hydraulic press cavity; 4) Start the large-tonnage hydraulic press to complete the pressing of a single electrode block.
[0050] 3. Electrode welding: Multiple electrode blocks are stacked and welded using a vacuum plasma welding box with argon protection to obtain a consumable electrode with a diameter of Φ420 mm.
[0051] 4. Primary smelting: The consumable electrode is welded with the auxiliary electrode of the same brand in a vacuum consumable furnace, and then the first smelting is carried out in a crucible with a diameter of Φ500mm. The smelting current is 10KA, the smelting voltage is 30V, the arc stabilization current is DC 7A, the vacuum degree is controlled to be ≤10.0Pa during the smelting process, and the cooling time after smelting is not less than 4 hours.
[0052] 5. Secondary smelting: The ingot head with a diameter of Φ500mm obtained after the first smelting is flattened by machine, turned around (head at the bottom and bottom at the top) and loaded into the furnace, and then smelted for the second time in a crucible with a diameter of Φ580mm. The smelting current is 14KA, the smelting voltage is 32V, the arc stabilization current is AC 12A / 8s, the vacuum degree is controlled to be ≤5.0Pa during the smelting process, and the cooling time after smelting is greater than 5 hours.
[0053] 6. Third smelting: The ingot with a diameter of Φ580mm obtained after the second smelting is turned upside down (with the head at the bottom and the bottom at the top) and loaded into the furnace, and the third smelting is carried out in a crucible with a diameter of Φ680mm. The smelting current is 12KA, the smelting voltage is 26V, the arc stabilization current is 9A / 6s, the vacuum degree is controlled to be ≤2.0Pa during the smelting process, and the cooling time after smelting is greater than 7 hours.
[0054] 7. The smelted ingot is machined and the riser is cut off to obtain a Ti1350 finished ingot with a diameter of Φ680mm.
[0055] Implementation Case 2: Φ780mm (weight 5-7 tons) ingot
[0056] 1. Raw material selection: Select sponge titanium, Al-85Mo master alloy, Al-70Cr master alloy, Al-85V master alloy, Al-75Nb master alloy, Ti-80Sn master alloy, Al bean, and sponge Zr with qualified ingredients as raw materials. The particle sizes of Al-85Mo, Al-85V, and Al-75Nb master alloys are controlled at ≤0.8mm, ≤3.0mm, and ≤1.2mm, respectively, and the maximum particle size of other master alloys does not exceed 12mm.
[0057] 2. Preparation of electrode blocks: Automatic mixing and large-tonnage vertical hydraulic press are used to press electrode blocks with a diameter of Φ480mm. The pressing of each electrode block includes the following four steps: 1) Add 4kg of sponge titanium to the bottom of the hydraulic press cavity and flatten it; 2) Mix half the weight of sponge titanium and intermediate alloy in a mixer and add them into the hydraulic press cavity; 3) Mix the other half the weight of sponge titanium and intermediate alloy in a mixer and add them into the hydraulic press cavity; 4) Start the large-tonnage hydraulic press to complete the pressing of a single electrode block.
[0058] 3. Electrode welding: Multiple electrode blocks are stacked and welded using a vacuum plasma welding box with argon protection to obtain a consumable electrode with a diameter of Φ480mm.
[0059] 4. Primary smelting: The consumable electrode is welded with the auxiliary electrode of the same brand in a vacuum consumable furnace, and then the first smelting is carried out in a crucible with a diameter of Φ580mm. The smelting current is 12KA, the smelting voltage is 32V, the arc stabilization current is DC 9A, the vacuum degree is controlled to be ≤10.0Pa during the smelting process, and the cooling time after smelting is not less than 4 hours.
[0060] 5. Secondary smelting: The ingot with a diameter of Φ580mm obtained after the first smelting is flattened, turned around (with the head at the bottom and the bottom at the top) and loaded into the furnace, and the second smelting is carried out in a crucible with a diameter of Φ680mm. The smelting current is 16KA, the smelting voltage is 34V, the arc stabilization current is AC 14A / 9s, the vacuum degree is controlled to be ≤5.0Pa during the smelting process, and the cooling time after smelting is greater than 5 hours.
[0061] 6. Third smelting: The ingot with a diameter of Φ680mm obtained after the second smelting is turned over (with the head at the bottom and the bottom at the top) and loaded into the furnace, and the third smelting is carried out in a crucible with a diameter of Φ780mm. The smelting current is 13KA, the smelting voltage is 28V, the arc stabilization current is 12A / 7s, the vacuum degree is controlled to be ≤2.0Pa during the smelting process, and the cooling time after smelting is greater than 7 hours.
[0062] 7. The smelted ingot is machined and the riser is cut off to obtain a Ti1350 finished ingot with a diameter of Φ780mm.
[0063] Finished ingot reference Figure 1 and Figure 2 Sampling was carried out for chemical composition analysis. The chemical composition of the main elements in the longitudinal direction of the ingot is shown in Table 1. The chemical composition test results of each element at nine points in the transverse direction of the ingot are shown in Tables 2 to 8 respectively. The composition of the ingot is uniform and fully meets the standard requirements.
[0064] Table 1 Chemical composition content of main elements in the longitudinal direction of the ingot (mass fraction %)
[0065]
[0066] Table 2 Al element content at nine points in the ingot transverse direction (mass fraction %)
[0067]
[0068] Table 3 Mo element content at nine points in the ingot transverse direction (mass fraction %)
[0069]
[0070] Table 4 V element content at nine points in the ingot transverse direction (mass fraction %)
[0071]
[0072]
[0073] Table 5 Nb element content at nine points in the ingot transverse direction (mass fraction %)
[0074]
[0075] Table 6 Cr element content at nine points in the ingot transverse direction (mass fraction %)
[0076]
[0077] Table 7 Zr element content at nine points in the ingot transverse direction (mass fraction %)
[0078]
[0079]
[0080] Table 8 Sn element content at nine points in the ingot transverse direction (mass fraction %)
[0081]
[0082] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a titanium alloy ingot, characterized in that: It includes the following steps: (1) Raw material selection: Select sponge titanium, Al-85Mo master alloy, Al-70Cr master alloy, Al-85V master alloy, Al-75Nb master alloy, Ti-80Sn master alloy, Al bean, and sponge Zr with qualified composition as raw materials, wherein the particle sizes of Al-85Mo, Al-85V, and Al-75Nb master alloys are controlled to be ≤0.8 mm, ≤3.0 mm, and ≤1.2 mm, respectively, and the maximum particle size of other master alloys is ≤12 mm; (2) Preparation of electrode blocks: Electrode blocks are pressed using an automatic mixing and large-tonnage vertical hydraulic press. The pressing of each electrode block includes the following steps: (2.1) Add a certain amount of titanium sponge to the bottom of the hydraulic press mold cavity and level it; (2.2) Mix half the weight of titanium sponge and master alloy in a mixer and add them into the mold cavity of the hydraulic press; (2.3) The mixer mixes the other half weight of titanium sponge and master alloy and adds them into the mold cavity of the hydraulic press; (2.4) Start the large-tonnage hydraulic press to complete the pressing of a single electrode block; (3) Electrode welding: Multiple electrode blocks are stacked and welded using argon protection in a vacuum plasma welding box to obtain a consumable electrode; (4) Primary smelting: The consumable electrode is welded with the auxiliary electrode of the same brand in a vacuum consumable furnace, and then smelted. The smelting current is 9-14KA, the smelting voltage is 29-35V, the arc stabilization current is DC 6A-10A, the vacuum degree is controlled to be ≤10.0Pa during the smelting process, and the cooling time after smelting is ≥4 hours; (5) Secondary smelting: After the first smelting, the ingot is turned over and loaded into the furnace. After auxiliary electrode welding, the second smelting is carried out. The smelting current is 13-18KA, the smelting voltage is 29-36V, the arc stabilization current is AC (10A-15)A / (6-10)s, the vacuum degree is controlled to be ≤5.0Pa during the smelting process, and the cooling time after smelting is greater than 5 hours; (6) Tertiary smelting: After the secondary smelting, the ingot is turned over and loaded into the furnace. After auxiliary electrode welding, the third smelting is carried out. The smelting current is 9-14KA, the smelting voltage is 24-36V, the arc stabilization current is (7A-17)A / (4-8)s, the vacuum degree is controlled to be ≤2.0Pa during the smelting process, and the cooling time after smelting is greater than 7 hours; (7) The smelted ingot is machined and the riser is removed to obtain the finished ingot.
2. The method for preparing a titanium alloy ingot according to claim 1, characterized in that: In the step (2.1), 2 kg of sponge titanium is added to the bottom of the hydraulic press cavity and flattened; in the step (3), a consumable electrode with a diameter of Φ420 mm is obtained; in the step (4), the first smelting is carried out in a crucible with a diameter of Φ500 mm, the smelting current is 10 KA, the smelting voltage is 30 V, and the arc stabilizing current is 7 A DC; in the step (5), the second smelting is carried out in a crucible with a diameter of Φ580 mm, the smelting current is 14 KA, the smelting voltage is 32 V, and the arc stabilizing current is 12 A / 8 s AC; in the step (6), the third smelting is carried out in a crucible with a diameter of Φ680 mm, the smelting current is 12 KA, the smelting voltage is 26 V, and the arc stabilizing current is 9 A / 6 s; in the step (7), the smelted ingot is machined, the riser is cut off, and the diameter is Φ680 mm to obtain a finished ingot.
3. The method for preparing a titanium alloy ingot according to claim 1, characterized in that: In the step (2.1), 4 kg of sponge titanium is added to the bottom of the hydraulic press cavity and flattened; in the step (3), a consumable electrode with a diameter of Φ480 mm is obtained; in the step (4), the first smelting is carried out in a crucible with a diameter of Φ580 mm, the smelting current is 12KA, the smelting voltage is 32V, and the arc stabilizing current is DC 9A; in the step (5), the second smelting is carried out in a crucible with a diameter of Φ680 mm, the smelting current is 16KA, the smelting voltage is 34V, and the arc stabilizing current is AC 14A / 9s; in the step (6), the third smelting is carried out in a crucible with a diameter of Φ780 mm, the smelting current is 13KA, the smelting voltage is 28V, and the arc stabilizing current is 12A / 7s; in the step (7), the smelted ingot is machined and the riser is cut off to obtain a finished ingot with a diameter of Φ780 mm.
4. A titanium alloy ingot manufactured according to the method for preparing a titanium alloy ingot according to any one of claims 1 to 3.
Citation Information
Patent Citations
Preparation method for large-sized TC21 titanium alloy ingot
CN104232994A
Ti6321 titanium alloy cast ingot smelting feeding method
CN109487092A
Vacuum consumable melting method for high-homogeneity titanium alloy
CN113604693A
Preparation method of Ti-1300 titanium alloy thin-wall pipe
CN115415357A
Titanium alloy consumable electrode and preparation method and application thereof
CN115505766A
Cited By
Welding method and auxiliary device for titanium alloy cast ingot during vacuum self-consuming secondary smelting
CN121467871A